The association between reproductive history and the multidimensional health of older adults in rural China and its gender differences: Evidence from the Chinese longitudinal healthy longevity survey - Yu, Changyong; Liang, Hang; Wang, Boyu; Liang, Fei; Liu, Erpeng; Xiang, Nan (Frontiers in Public Health, 2022)
Background: Few studies have examined the association between reproductive history and the multidimensional health of older adults with more diverse reproductive histories and poorer health status in rural China. The purpose of this study is to explore the effect of parity, sex ratio of children and late childbearing on multidimensional health and its gender differences. Methods: The analytical sample consisted of 3377 older adults in rural China who participated in the Chinese Longitudinal Healthy Longevity Survey (CLHLS) in 2018. Linear regression models were applied to estimate the relationship between reproductive history and multidimensional health, with separate models for each indicator of health outcomes. Results: Older adults in rural areas with greater parity were more likely to have better cognitive function (β = 0.409, 95% CI: 0.255 to 0.563), fewer Activities of Daily Living (ADL) limitations (β = -0.085, 95% CI: -0.137 to -0.034) and symptoms of depression (β = -0.396, 95% CI: -0.577 to -0.216). The social mechanism of intergenerational support from children later in life partly explained the positive effect of parity. Late childbearing had negative effects on cognitive function (β = -1.220, 95% CI: -1.895 to -0.545), ADL (β = 0.253, 95% CI: 0.028 to 0.478) and symptoms of depression (β = 1.025, 95% CI: 0.237 to 1.812). Women were more likely to be influenced by the positive effect of parity; the association between late childbearing and health was only significant in the male group. Conclusions: Parity and late childbearing are associated with cognitive function, activities of daily living, and symptoms of depression in the older adults in rural China. Older adults with more children might be in better health, and this finding is especially significant in women. However, late childbearing had a negative effect on multidimensional health, especially for men. The social mechanism and gender differences between reproductive history and health need to be further explored.